Elaboración del estudio de pre-factibilidad para el montaje de una empresa de consultoría en sostenibilidad de empresas hoteleras Colombianas (2015)
This document presents the pre-feasibility study carried out for the Assembly of a Sustainability Consulting Company of Colombian Hotel Companies; With this one, the aim is to study holistically the context in which the company that would be the product of the project would operate, in order to finally answer the question: is the project viable for its Stakeholders? To answer this question, the project team has carried out the following work: analysis of strategic alignment, market studies, technical studies, environmental studies, administrative studies, cost and benefit studies, budgets, investment and financing, and finally, the financial evaluation of the project. This work has been carried out at a pre-feasibility level, based on the research and knowledge acquired during the Specialization in Development and Integral Project Management of the Colombian School of Engineering Julio Garavito.